(untitled) (European Journal of Pure and Applied Mathematics, 2025)
This article presents new classes of multifunctions called upper weakly s-(τ_1,τ_2)-continuous multifunctions and lower weakly s-(τ_1,τ_2)-continuous multifunctions. Furthermore, several characterizations of upper weakly s-(τ_1,τ_2)-continuous multifunctions and lower weakly s-(τ_1,τ_2)-continuous multifunctions are discussed.